Screening of M5 Generation Mutant Lines for Charcoal Rot Resistance in Sorghum [Sorghum bicolor (L.) Moench] - Mohinuddin, D. Khaja; Girish, G.; Suvarna; Badigannavar, Ashok; Yogeesh, L. N.; Govindappa, M. R.; Kumar, V. Anand; Kumar, A. Ravi (International Journal of Bio-resource and Stress Management, 2023)
This study was carried out in augmented design during rabi 2021 (November‒May) at Agriculture research station, Hagari, Karnataka, India to identify the charcoal rot resistant mutant line. Total 200 mutants and 7 checks were used to study the charcoal rot resistance in the present experiment. Charcoal rot is a major disease in the dry sorghum-growing regions of Asia, Africa, Americas and Australia. Charcoal rot disease is caused by Macrophomina phaseolina (Tassi) Goid. It appears in severe form on the improved varieties in hot dry weather with soil moisture stress. The process of mutation is recognized as one of the driving forces of evolution. Induced mutation breeding is a relatively quick method of creating variability in quantitatively inherited traits between plants. The parameters used in charcoal rot studies were lodging per cent, mean number of nodes crossed, mean length of spread and Charcoal rot index (CRI). The screening results revealed that 66 mutant lines shown moderate resistant reaction compared to the resistant check DSV-4 (0.5) and E-36-1 (0.27), among them eight mutants had exact only one node crossed by the pathogen. These mutant lines exhibited comparatively lowest number of mean nodes crossed. 84 mutant lines shown moderate resistant response to charcoal rot index trait. These resistant lines can be used for further confirmation and also for future resistant breeding programme.